Influence of temperature and addition of fiber in the flow behavior of orange juice - Siche, Raul (2012)
In this study the influence of the addition of orange fiber in the flow behavior of orange juice was evaluated, using for this the Herschel-Bulkley model parameters. It was observed that the flow behavior of the juices changed due to the addition of fiber, from Newtonian to Pseudoplastic when its fiber content was 5% and the temperature changed from 30 °C to 20 °C, and from Pseudoplastic to Herschel-Bulkley when its fiber content was 12.5% and the temperature changed from 10 °C to 0 °C. The increase in fiber content resulted in a progressive increase of consistency and a decrease of the flow behavior index.